Trichomicin Suppresses Colorectal Cancer via Comprehensive Regulation of IL-6 and TNFα in Tumor Cells, TAMs, and CAFs - Zhao, Xi; Qi, Xiaoqiang; Lian, Wenrui; Tong, Xin; Wang, Hua; Su, Liya; Wei, Ping; Zhuang, Zhuochen; Gong, Jianhua; Bai, Liping (Frontiers in Pharmacology, 2020)
Trichomicin, a small-molecule compound isolated from fungi, has been identified with bioactivity of antitumor. In this study, a colon cancer subcutaneous mice model was used to evaluate the antitumor effects of Trichomicin in vivo. Treatment with Trichomicin significantly inhibited tumor growth in a xenograft mouse colon cancer model. The underlying molecular mechanism has also been investigated through the quantification of relevant proteins. The expression levels of IL-6 and TNFα were reduced in tumor tissues of mice treated with Trichomicin, which was consistent with results of in vitro experiments in which Trichomicin suppressed the expression of IL-6 and TNFα in tumor and stromal cells. In addition, Trichomicin inhibited TNFα-induced activation of NF-κB and basal Stat3 signaling in vitro, which resulted in reduced expression of the immune checkpoint protein PD-L1 in tumor and stromal cells. Conclusively, Trichomicin, a promising new drug candidate with antitumor activity, exerted antitumor effects against colon cancer through inhibition of the IL-6 and TNFα signaling pathways.